Prepupal diapause synchronizes adult emergence in the pine processionary moth Thaumetopoea pityocampa (Lepidoptera: Notodontidae). (1st June 2018) - Salman, Md Habibur Rahman; Giomi, Folco; Laparie, Mathieu; Lehmann, Philipp; Battisti, Andrea
Abstract: Insects with short‐lived adults must synchronize their emergence to maximize fitness. However, pre‐imaginal development time often varies among individuals as a result of exposure to varied abiotic and biotic factors; therefore, mechanisms adjusting pre‐imaginal development time are expected. Larvae of the pine processionary moth feed throughout the winter and conclude their development with characteristic processions in spring, leaving the trees to pupate in soil. The procession period can be as long as 2 months in some regions because of prior desynchronization of larval colonies, whereas the emergence period of the adults in summer remains short (less than 1 month). Through weekly sampling of larvae leaving trees to pupate in soil and subsequent rearing under field and laboratory conditions, it was observed that early prepupae waited longer than late prepupae before moulting into pupa. The differential duration of the prepupal stage was independent of temperature conditions and allowed resynchronization of colonies and overlapping emergences. The prepupal phase therefore appears to be critical for understanding the regulation of adult emergence of this important pest insect.